Repeated Etching Cycles of Resin Infiltration up to Nine Cycles on Demineralized Enamel: Surface Roughness and Esthetic Outcomes-In Vitro Study - Dayang Fadzlina Abang Ibrahim; Noren Nor Hasmun; Yih Miin Liew; Annapurny Venkiteswaran (MDPI AG, 2023)
Resin infiltration (RI) is used to mask enamel opacities. There are three recommended etching cycles. However, anecdotal evidence suggests that favorable esthetics outcomes can be obtained by increasing the etching cycles. This study aimed to evaluate the effects of repeated etching cycles during RI application on esthetic changes and surface roughness of demineralized enamel at multiple treatment stages. Artificial demineralization was prepared on the buccal surface of ninety sound extracted premolars. The teeth were divided into nine groups (n = 10); with each consecutive group having one additional etching cycle up to nine etching cycles. Resin infiltrant was performed twice, first for 3 min (Resin 1) and again for 1 min (Resin 2). Surface roughness and esthetic changes were assessed using a profilometer (Ambios XP-200) and Minolta spectrophotometer, respectively, at baseline (sound enamel), etching, resin 1, resin 2, 7 days, and 28 days post resin applications. Data were analyzed with two-way ANOVA (p < 0.05). There was a significant interaction between the different stages and various groups of etching cycles on surface roughness, F(48, 126) = 3.48, p < 0.001. There was a significant interaction between the different stages and various groups of etching cycles on color changes, F(4, 126) = 1.177, p = 0.045. The surface roughness of demineralized enamel infiltrated with RI was less than that of sound enamel (baseline). There is a significant difference in color changes between resin 1 and resin 2 (p < 0.05). After five etching cycles, RI improved the esthetic of the color of teeth similar to the baseline. Surface roughness and color changes remained constant for 28 days. RI can be considered an effective and predictable treatment option for the restoration of early enamel lesions owing to its better surface characteristics and reliable masking effects. The color stability and surface roughness stay unaltered for up to 28 days.